A research note on the association between work–family conflict and job stress among Chinese prison staff. Issue 7 (9th August 2017) - Liu, Jianhong; Lambert, Eric G.; Jiang, Shanhe; Zhang, Jinwu
ABSTRACT: Job stress, which has been found to have numerous negative effects on U.S. correctional staff, occurs as a result of stressors in the work environment. Recent research in the U.S. suggests that work–family conflict (e.g. time-based conflict, strain-based conflict, behavior-based conflict, and family-based conflict) may contribute to job stress for correctional staff. This exploratory study examined how different dimensions of work–family conflict were associated with job stress by surveying 322 staff at 2 Chinese prisons, 1 for male inmates and 1 for female inmates, in Guangzhou. An Ordinary Least Squares regression equation was computed with the job stress index as the dependent variable, and the personal characteristics (i.e. age, tenure, gender, educational level, and marital status) and the four work–family conflict variables as the independent variables. The independent variables explained about 49% of the observed variance in the job stress variable. The personal characteristics, time-based conflict, and family-on-work conflict did not have a statistically significant association with job stress in the multivariate analysis, but both strain-based conflict and behavior-based conflict had negative associations.